In‐Plane Self‐Turning and Twin Dynamics Renders Large Stretchability to Mono‐Like Zigzag Silicon Nanowire Springs. (24th May 2016) - Xue, Zhaoguo; Xu, Mingkun; Li, Xing; Wang, Jimmy; Jiang, Xiaofan; Wei, Xianlong; Yu, Linwei; Chen, Qing; Wang, Junzhuan; Xu, Jun; Shi, Yi; Chen, Kunji; et al.
Abstract : Crystalline Si nanowire (SiNW) springs, produced via a low temperature (<350 °C) thin film technology, are ideal building blocks for stretchable electronics. Herein, a novel cyclic crystallographic‐index‐lowering self‐turning and twin dynamics is reported, during a tin‐catalyzed in‐plane growth of SiNWs, which results in a periodic zigzag SiNW without any external parametric intervention. More interestingly, a unique twin‐reflected interlaced crystal‐domain structure has been identified for the first time, while in situ and real‐time scanning electron microscopy observations reveal a new twin‐triggering growth mechanism that is the key to reset a complete zigzag growth cycle. Direct "stress–strain" testing of the SiNW springs demonstrates a large stretchability of 12% under tensile loading, indicating a whole new strategy and capability to engineer mono‐like SiNW channels for high performance stretchable electronics. Abstract : Cyclic crystallographic‐index‐lowering self‐turning and twin dynamics leads to periodic zigzag growth of in‐plane Si nanowires, while in‐situ scanning electron microscopy observations reveal a new twin‐triggering growth mechanism that is the key to reset a complete zigzag growth cycle. Direct "stress‐strain" testing confirms a linear stretchability of 12% under tensile strain, indicating a promising candidate for high performance stretchable electronics.